1999
DOI: 10.1366/0003702991945452
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation Mass Spectroscopy of Nineteenth Century Daguerreotypes

Abstract: Laser desorption mass spectroscopy has been used to characterize both modern and ∼ 150-year-old daguerreotypes. Such investigations are a necessary prelude to attempts to clean them of tarnish and other contaminants by laser ablation of the surface layers. Both positive- and negative-ion time-of-flight spectra were obtained following YAG laser ablation/desorption at 1064, 532, and 355 nm. Major peaks obtained from several daguerreotypes reveal expected elements from the substrate (Ag, Cu) as well as the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…This plume is the result of the molecular species being removed from the surface creating a ''plasma cloud" above the sample face. If the density of the plume is high enough, it can lead to gas phase reactions [8] and thus the peaks of the resulting spectra will no longer truly represent the glass composition, though this kind of higher-power arrangement is often [9][10][11][12][13] used for elemental analysis. We never saw visual evidence of a plume, and we also note that such a plume would drastically alter the resolution of our instrument, a phenomenon which was never observed.…”
Section: Ms-tofmentioning
confidence: 99%
“…This plume is the result of the molecular species being removed from the surface creating a ''plasma cloud" above the sample face. If the density of the plume is high enough, it can lead to gas phase reactions [8] and thus the peaks of the resulting spectra will no longer truly represent the glass composition, though this kind of higher-power arrangement is often [9][10][11][12][13] used for elemental analysis. We never saw visual evidence of a plume, and we also note that such a plume would drastically alter the resolution of our instrument, a phenomenon which was never observed.…”
Section: Ms-tofmentioning
confidence: 99%
“…and compared with the number of daguerreotypes reported to have been produced in the 19th century, only a relatively small number of plates have been examined beyond conventional optical microscopy with spectroscopic techniques, scanning electron microscopy (SEM), and other nanoscale imaging methods capable of examining and characterizing the nanostructures on their surface (6,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Unfortunately, time and exposure to the elements have irreversibly altered 19th-century daguerreotype images, making it difficult to use them to characterize their properties.…”
Section: Significancementioning
confidence: 99%
“…Sulfur and chlorine are the two elements with the greatest association with daguerreotype image deterioration in the forms of silver sulfide [5] and silver chloride [6], respectively. Several analytical techniques [3,[7][8][9][10] have been used to further the understanding of the tarnish composition for conservation, preservation, storage, and display of these artifacts. Currently, there is no clear explanation for the origin of tarnish features, nor is there a consensus on the most effective conservation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analysis [1][2][3][4][5][6][7][8][9][10][11] has suggested that one possible source of the tarnish could be the deterioration of the cover glass used to protect the daguerreotypes from chemical and/or atmospheric conditions, dust and debris, or from mechanical damage. For example, Barger [12] suggested that deterioration of the cover glass as well as the geometry and composition of the frame might lead to deterioration of daguerreotypes.…”
Section: Introductionmentioning
confidence: 99%